Production of Biomass and Bioactive Compound as a-Glucosidase Inhibitor Activities Simplisia Cat Whiskers (Orthosiphon aristatus) at Fertilization and Differences Harvest Rotation Time - Malasari, Silvina; Miska, Moh. Ega Elman; Fauziyah, Qonitah; Selita, Neni (International Journal of Agriculture System, 2024)
Cat whiskers are traditional medicinal plants with bioactive compounds like flavonoids like sinensetin. The development of cat whiskers as a medicinal plant is still constrained by the quality of the simplisia. Fertilization and harvesting are essential aspects of the cultivation of medicinal plants. The research aims to determine the proper fertilization and harvest rotation time differences to produce biomass production and bioactive compound simplisia in cat whisker leaves. The method used was a Randomized Complete Block Design composed of two factors. The first factor was harvest rotation, consisting of four and six levels. The second factor was fertilization, composed of three levels, namely 100 g Indigenous Arbuscular Mycorrhizal Fungi (AMF) inoculum, 2.1 g Urea (N fertilizer) & 2.7 g SP-36 (P fertilizer), and a combination of 100 g Indigenous AMF inoculum + 2.1 g Urea (N fertilizer) & 2.7 g SP-36 (P fertilizer). The results showed that the highest simplisia biomass production was obtained by giving a combination fertilizer (Indigenous AMF, N & P). In contrast, the highest simplisia bioactive compound production was obtained with indigenous Arbuscular Mycorrhizal Fungi (AMF) fertilizer or a combination fertilizer (Indigenous FMA, N & P). Production of biomass and bioactive compounds of cat whisker plants simplisia can be done by harvesting earlier every four weeks or extending the harvesting time to every six weeks.